Entre diálogos silenciados e o pseudodiálogo: denúncias e anúncios no processo de construção do currículo de Biologia nos centros de educação de jovens e adultos de Goiás - Ribeiro, Renato Antônio (2022)
Having as theoretical support the work of Paulo Freire and its assumptions, this thesis aimed to understand how the process of curricular construction in the EJA offered in the EJA (Centers of Youth and Adult Education of Goiás) of Goiás, problematizing the dialogue that is established in this process in order to provide curricularization subsidies in the modality. The empirical part of the research took place in institutions that offer the EJA as a priority in the state of Goiás (the JaSC), based on interviews with 12 biology professors working in these institutions and with 23 students. The research problem that guides this thesis started from the following question: What is the perspective of dialogue in the curricularization process of the EJA offered in the JaSC of Goiás? The EJA in Brazil faces its limit situations and the Freiriana hope – of collective struggle and resistance, not waiting – is necessary, especially to rethink curricular organizations in the modality that yearn to meet the interests of the oppressed – the student working class. These students dream and see in the EJA an engine of hope and history as a possibility, thus revealing a hidden conception: the modality is an engine of transformation of society, nourishing dreams and hope. It is important to rethink a formative model – and in it the curricular organization – that directs this conception towards liberation, emancipation and humanization of the subjects. Thus, this research designed to point out some proposal for change, some possible dream, some unpublished-feasible for the EJA curriculum, without, however, methodologicalizing Paulo Freire, contrary to its principles. There is also the defense of biology teaching based on a political act based on the dialogue between the "knowledge of experience made" of students of the EJA and the systematized biological knowledge, here considered those that make up the conceptual status of the structuring theories of Biology presented by Nascimento Jr. (2010) – cellular theory, theory of internal balance (homeotase), gene theory (inheritance), ecosystem theory and theory of evolution – but without disregarding the other statutes – the ontological, the epistemological and the social history. The discussions undertaken in this study point out that the process of biology curricularization in the EJA in the state of Goiás is between the use of authentic Freiriano dialogue, which is critical, democratic, seeks transformation and believes in men, and pseudodialogue, which is mute, unbelieving, alienated and uncritical. We admit as a valid and possible way to freireanear the curricula of the EJA from the reinvention and recontextualization of the Freriano assumptions and their dialogical pedagogy in the individual scope of the EJA institutions, contributing to the humanization of the subjects who do the modality. It is necessary to seek true dialogue from freiriana radicality in the curricular construction of biology in the EJA.